The experience of divine struggle following child loss: The Case of Israeli bereaved Modern-Orthodox parents. Issue 6 (3rd July 2022) - Frei-Landau, Rivi; Hasson-Ohayon, Ilanit; Tuval-Mashiach, Rivka
Abstract: Child loss may undermine one's faith. Whereas much is known about religion's role following loss, less is known about the experience of divine struggle—namely, struggling with complex God-related emotions/beliefs—particularly among diverse sociocultural samples. Employing a narrative approach, we interviewed 20 bereaved Modern-Orthodox parents. Analysis revealed three types of divine struggle (explicit, implicit/silenced, none) differentiated by four categories: core emotional experience, response type, significance of faith in the coping process, and the impact of grief-induced divine struggle on parent-God relationship. Findings emphasize the need for culturally-sensitive inquiry of divine struggle, that divine struggle may be silenced, and therapists' awareness is critical.